A Critique of the Philosophical Presuppositions of Cognitive Psychology. (2nd October 2022) - Yueyu, Shu; Shenchun, Gao
Abstract: In the historical interaction of science and philosophy, empirical science has used cumulative research to shed new light on how the science of philosophy understands fundamental scientific issues. As an effort of self-renewal, the initial impetus for the birth of cognitive science was dialogue among disciplines, with a view to making it possible to unlock the mysteries of cognition. In other words, cognitive science was to pave the way for fundamentally updating the philosophical premises of the science of mind or even making possible a new scientific worldview. As a branch of cognitive science, psychology was to have contributed to the renovation of the ontological, methodological and scientific worldview of cognitive science through its unique interpretation of human nature. However, in the course of the development of cognitive science and psychology, psychology has failed to employ its disciplinary endeavors to renew the ontology, methodology and values of the philosophical foundations of cognitive science, and has also failed to contribute to the promotion of cognitive science. On the contrary, cognitive science's mechanistic worldview and positivist methodology are the sole determinants of the background of cognitive science that shapes psychology's model of development—that is, cognitive psychology (if one sees cognitive psychology as a concrete manifestation of the interaction of cognitive science and psychology). This study examines cognitive psychology's ontological, methodological and value presuppositions and scientific worldview and reflects on the blind and passive nature of the discipline's development. Moreover, from a history of science perspective, it considers how the development of this discipline can contribute to the renewal of scientific concepts in the philosophy of science through the interaction of the mature natural sciences and philosophy and thence provide possibilities for handling the relationship between psychology and philosophy in psychology's future development.